Neoadjuvant chemoradiation (modified Eilber protocol) versus adjuvant radiotherapy in the treatment of extremity soft tissue sarcoma. Issue 4 (3rd March 2016) - Lehane, Chris; Ho, Frederick; Thompson, Stephen R; Links, David; Lewis, Craig; Smee, Robert; Parasyn, Andrew; Friedlander, Michael; Williams, Janet; Crowe, Phil
Abstract: Background: Local control for extremity soft tissue sarcomas (STS) requires surgery combined with radiotherapy, usually given pre‐operatively or post‐operatively. The modified Eilber protocol, a neoadjuvant chemoradiation regimen, has been reported with excellent local control rates. This retrospective single‐centre study compared outcomes for patients treated with the modified Eilber protocol with those treated with standard adjuvant radiotherapy. Methods: Patients with a diagnosis of extremity STS were retrospectively reviewed from the Prince of Wales Hospital Sarcoma Database from 1995 to 2012. Sixty‐three patients underwent curative surgery with either neoadjuvant Eilber chemoradiotherapy (Eilber) or adjuvant radiotherapy (Adjuvant). Results: Twenty‐nine patients were treated with modified Eilber protocol. Thirty‐four patients received adjuvant radiotherapy. Three patients (10%) in the Eilber group and five patients (15%) in the Adjuvant group developed local recurrence ( P  = 0.87). Major acute wound complications were noted in four patients in each group ( P  = 0.55). One patient (3.4%) in the Eilber group developed Grade 3 or 4 late toxicities after 1 year compared with nine patients (27%) in the Adjuvant group ( P  = 0.02). Conclusion: Neoadjuvant chemoradiation (Eilber protocol) provided similar rates of local control when compared with adjuvant radiotherapy. Acute wound complication rates were similar but there was less severe late toxicity in the Eilber group. Abstract : Synopsis : The modified Eilber protocol, a neoadjuvant chemoradiation regimen used for extremity soft tissue sarcoma has been reported with excellent local control rates. This paper assesses local control rates and late toxicities of patients treated with this protocol.